NR2B Expression in Rat DRG Is Differentially Regulated Following Peripheral Nerve Injuries That Lead to Transient or Sustained Stimuli-Evoked Hypersensitivity - Norcini, Monica; Sideris, Alexandra; Adler, Samantha M.; Hernandez, Lourdes A. M.; Zhang, Jin; Blanck, Thomas J. J.; Recio-Pinto, Esperanza (Frontiers in Molecular Neuroscience, 2016)
Following injury, primary sensory neurons undergo changes that drive central sensitization and contribute to the maintenance of persistent hypersensitivity. NR2B expression in the Dorsal root ganglia (DRG) has not been previously examined in neuropathic pain models. Here we investigated if changes in NR2B expression within the DRG are associated with hypersensitivities that result from peripheral nerve injuries. This was done by comparing the NR2B expression in the DRG derived from two modalities of the spared nerve injury (SNI) model, since each variant produces different neuropathic pain phenotypes. Using the electronic von Frey to stimulate the spared and non-spared regions of the hindpaws, we demonstrated that sural-SNI animals develop sustained neuropathic pain in both regions while the tibial-SNI animals recover. NR2B expression was measured at Day 23 and Day 86 post-injury. At both days sural-SNI displays strong hypersensitivity. At Day 23 and Day 86, tibial-SNI respectively displays 50% and 100% recovery from post-injury-induced hypersensitivity. In tibial-SNI at Day 86, but not at Day 23 the perinuclear region of the neuronal somata displayed an increase in NR2B protein. This retention of NR2B protein within the perinuclear region, which will render them nonfunctional, correlates with the recovery observed in tibial-SNI. In sural SNI at Day 86 displayed an increase in NR2B mRNA which correlates with the development of sustained hypersensitivity following sural-SNI. The increase in NR2B mRNA was not associated with an increase in NR2B protein within the neuronal somata. The latter may result from a decrease in kinesin Kif17, since Kif17 mediates NR2B transport to the soma’s plasma membrane. In both SNIs, microglia/macrophages showed a transient increase in NR2B protein detected at Day 23 but not at Day 86; which correlates with the initial post-injury induced hypersensitivity in both SNIs. In tibial-SNI at Day 86, but not at Day 23 satellite glia cells (SGCs) displayed an increase in NR2B protein. This study is the first to characterize of cell-specific changes in NR2B expression within the DRG following peripheral nerve injury. We discuss how the observed NR2B changes in DRG can contribute to the different neuropathic pain phenotypes displayed by each SNI variant.